Dispel the illusion of holiness The implicit aspect of the Husayni renaissance (Journal of Misan Researches, 2021)
This research wants to give more attention to the implicit side, which was targeted Imam Hussein in his great reform, the illusion of holiness, whether the concept of the group, which some invoked the inadmissibility of violating or leave it and dispel, incurring the texts of the Koran interpretation in affectation and Not hidden credulity, or texts Hdithih look like effects the situation and Choke, or this holiness related to the ruling power, then an officer for this consensus and maintain, or after the other value of the sanctity of supreme derives its dominance from the perspective of the succession of the Prophet and the endorsement of the Islamic group them and allegiance to it, which in all cases, the holiness of illusionary produced and focused presence A form of absolute act of historical Islam-The Caliphs. Here is a capacity point of view of the renaissance of Husseiniya, to deal with two dimensions overlap and perhaps opposite directions at the same time, two purpose frank and direct representatives of the Confrontation the Umayyad power, the purpose that lies behind this confrontation, a conceptual structure of historical Islam or the image-distorting Islam, both in the bloc of the Umayyad or in community bloc (universality Islamic group except owners of the Imam).